Miller's marine war risks - Caplin, Oliver; Miller, Michael D. (Writer on marine insurance); Davey, James (Law teacher); Davey, Michael (Lawyer) (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Miller's Marine War Risks is the only book devoted to drawing together and analysing the insurance of commercial shipping against war risks. It merges analysis of the legal principles, case law, and legislation with the practice of the insurance market in order to provide commentary on difficult questions concerning liabilities, claims, and coverage. With global events becoming more uncertain in the Gulf and elsewhere, the updating of Michael Miller's classic text will be of great use to legal practitioners, the insurance market, and the shipping industry throughout the world"--
The history of the war risks policy -- The underwriters -- The premiums -- Cancellation and automatic termination of cover clause -- The insured perils : an overview -- War -- Civil war -- Revolution, rebellion, insurrection . . . -- . . . or civil strife arising therefrom . . . -- . . . or any hostile act by or against a belligerent power -- Capture -- Seizure -- Arrest, restraint, detainment . . . -- . . . and the consequences thereof or any attempt thereat -- Derelict mines, torpedoes, band weapons of war -- Strikers, locked-out workmen or persons taking part in labour disturbances, riots or civil commotions -- Riots, civil commotions -- Any terrorist . . . -- . . . .or any person acting maliciously or from a political motive -- Piracy -- Confiscation and expropriation -- Sue and labour -- Exclusions -- War risks and marine insurance legislation -- Total loss and notice of abandonment -- Held covered -- Wilful misconduct and fraudulent claims -- The proximate cause -- Cargo war and strikes clauses -- Containers -- War risk insurance in time of war.
OCLC-licensed vendor bibliographic record.
Keywords: Marine insurance -- Great Britain -- War risks; Marine insurance -- Law and legislation -- Great Britain; LAW / Maritime